(3eaGJjM GdTQGFYs - (3GdcGTj, GdcGTj, eMSf GdajV, eMSf Hf eQJVi Hf ajV Gddg eMehO GdcGTj, J (B1090(3g` (B1680(3es
(3ChdgG (B:s
(3ChdgG(B: (3jSJMH GdGUMGQ HgPg GdUdGI aj ZjQ ecI heHGTQI GdCQV hGdSLhO YdjgG hCf dG jfbd GdefHQ ef GdLGeY hCf jWYe bHd NQhLg aj GdaWQ hHYO YhOg aj GdCVMis
(3BNQgG (B:s
(3BNQgG(B: (3haj GdNHQ(B: (3dG jfHZj GdUjGM Ydi GdejJ hdG Tb GdKjGH hgh eY VYag aXGgQg GdcQGgI Ohf GdJMQje(B. (3eaJGM(B: (3jSJMH GdGgOGA djdI GdOafs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B5: 290s
(3GdPQjYI, L (B21: 196s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis